Evaluation of Usage and Usability of Electronic Journals - Mounissamy, P.; Swaroop Rani, B. S. (Journal of Information and Knowledge, 2005)
In the era of digital libraries, Web-based electronic databases have become important resources for education and research. Digital libraries of academic institutions started to subscribe to number of electronic journals to meet the expectation of the users, because accessing the web has become very convenient. Electronic journals usage measurement is completely different from that of books usage measurement. This research article presents, problems experienced, usage, usability, and users’ satisfaction in accessing electronic journals.